The Influence of the Mimicry-Memorization (MIM-MEM) Method on EFL Young Learners’ Vocabulary Mastery - Putri, Winda; Akbarjono, Ali; Martina, Feny (Yayasan Darussalam Bengkulu, 2022)
This study aims to determine whether there is an influence of the Mimicry-Memorization (MIM-MEM) Method on EFL Young Learners’ Vocabulary Mastery at SDIT AL-AHSAN Seluma. This research uses Quasi-Experiment method with Time Series design. The researcher decided to conduct an experiment in class 5 with a total of 27 students. In the process of collecting data, the researcher conducted a pretest and posttest three times. From the results of this study, the students’ average pretest score was 77.33 and the posttest average was 90.81, which means that the posttest score was higher than the pretest score. So it can be concluded that the application of the Mimicry-Memorization (MIM-MEM) method has a significant effect on EFL Young Learners’ Vocabulary Mastery